Regional differences of coffee cultivation in Brazil - Coltro, Leda; Mourad, Anna Lúcia; Oliveira, Paula A.P.L.V.; Andrade, José Paulo B.O. (Coffee Science - ISSN 1984-3909, 2012)
Brazil is one of the major coffee producers in the world, because of this, the goal of this study was to assess the regional differences of coffee cultivation for the reference crops 2001/2002 and 2002/03 by means of a life cycle assessment (LCA) in order to generate detailed production inventory data as well as quantify the potential environmental impacts of this crop. All information considered in this study (use of water, fossil based energy, fertilizers, pesticides and correctives) was taken from data collected from the producing farms. Four Brazilian coffee producer regions located at the Southeastern region were evaluated: Sul de Minas Gerais and Cerrado Mineiro in Minas Gerais State, and Mogiana and Alta Paulista regions in São Paulo State. The data refer to a production of 25.2 million kg of green coffee. Depending on the considered region, the production of 1,000 kg of green coffee requires, on average, approx. 9,300 to 13,000 kg of total energy, 70 to 130 kg of diesel, 6,500 to 12,700 kg of process water, 270 to 340 kg of fertilizers (NPK), 2.0 to 13.0 kg of pesticides, 230 to 600 kg of correctives, and yield around 1,600 to 1,900 kg/ha. Despite 20% of the coffee growers showing a good environmental performance, i.e. consumption of pesticides, fertilizers and correctives lower than the regional averages, this study has also identified some farms that can probably reduce the amount of some inputs and enhance their environmental performance.